Simple and efficient conversion of cellulose to γ-valerolactone through an integrated alcoholysis/transfer hydrogenation system using Ru and aluminium sulfate catalysts. Issue 23 (16th November 2018) - Huang, Yao-Bing; Yang, Tao; Luo, Yu-Jia; Liu, An-Feng; Zhou, Yi-Han; Pan, Hui; Wang, Fei
Abstract : The conversion of cellulose to GVL was achieved through a one-pot reaction by integrating the alcoholysis and transfer hydrogen processes under microwave condition. Abstract : The direct conversion of cellulose to specific chemicals represents an important but challenging area that attracts much attention. In this study, we report, for the first time, a one-step conversion of cellulose to γ-valerolactone (GVL), a platform molecule with multiple applications, by integrating alcoholysis and transfer hydrogenation systems over mixed metal salt and Ru catalysts without external hydrogenation. A maximum GVL yield of 51.2% was obtained at 180 °C for 70 min reaction time with microwave heating. The metal salt effectively catalyzed cellulose alcoholysis to generate levulinate in isopropanol, which was also the hydrogen donor for the subsequent catalytic transfer hydrogenation of levulinate to GVL over the Ru/ZrO2 catalyst. It was found that the types of metal center and support material had a significant influence on the reactivity of the catalyst for the catalytic transfer hydrogenation (CTH) reaction, i.e., concerning the existence of sulfuric acid species and water in the reaction system. Microwave heating was demonstrated to be an effective method for cellulose-to-GVL conversion as compared to conventional oil heating, through drastically reducing the reaction time and avoiding decomposition of the reagents. The catalysts were successfully recycled and reused with high reactivity. Finally, the system was also applied to the synthesis of GVL from real biomass, demonstrating the high applicability and potential of the catalytic system for industrial production.